Restricting and facilitating factors in physical activities of - Tabarsi, B; Safavi, M; Valayi, N; Milashari, J (Advances in Nursing & Midwifery, 2008)
Background The increasing incidence of cardiovascular diseases and preventive or aggravating factors associated with it such as physical activities, feeling of malaise, stress, lack of well-being require ongoing investigations. Purpose This descriptive study was conducted to identify factors associated with physical activities in cardiac patients referring to health settings in Tehran. Methods 400 patients were selected sequentially by a random multistage sampling method. A questionnaire in 3 parts including demographics, type of physical activities and restricting as well as facilitating factors was used for data collection. Different statistical tests were used for data analysis. Results Most patients (66.8%) had low to moderate daily activities and low to moderate exercise (70.4%). Restricting factors for physical activities included feeling of malaise (41%) and stress (35.7%). Facilitating factors including feeling of wellness and self-efficacy in exercise were inaccessible for 64.7% and 74.5% respectively. A significant relationship was found between restricting factors (P<0.005) as well as lack of facilitating factors (0.05) and physical activities. Conclusion Daily physical activities and exercise in cardiac patients are inadequate and worrying. The most significant factors in this regard include feeling of malaise, stress and lack of such facilitating factors as feeling of wellness and self-efficacy in exercise. Keywords: Cardiovascular diseases, Daily physical activities, Exercise, Restricting factors, Facilitating factors.